Ukuran Perusahaan Sebagai Pemoderasi Pengaruh Sustainability Reporting Pada Nilai Perusahaan - Puspita, Ni Wayan Ita; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 34 No 11 (2024)DO - 10.24843/EJA.2024.v34.i11.p19, 2024)
The purpose of this study is to examine the effect of sustainability reporting on firm value and the ability of firm size to moderate the influence of sustainability reporting on company value. This research was conducted on SRI-KEHATI-indexed companies for the 2017-2021 period using the purposive sampling method. The results of this study are sustainability reporting doesn’t affect firm value and the size of the company hasn’t been able to strengthen the influence of sustainability reporting on company value. The limitation in this study haven’t classified the type of industry issuers. Thus, the implications of this study haven’t been able to provide empirical evidence regarding Signal Theory and Contingency Theory and haven’t been able to be considered by investors and potential investors to make investment decision by looking at sustainability reports.